Exploration of the key microbes and composition stability of microbial consortium GF-20 with efficiently decomposes corn stover at low temperatures - Xiao-fang YU; Qinggeer BORJIGIN; Ju-lin GAO; Zhi-gang WANG; Shu-ping HU; Naoganchaolu BORJIGIN; Zhen WANG; Ji-ying SUN; Sheng-cai HAN (Journal of Integrative Agriculture, 2019)
The microbial consortium GF-20 (GF-20) can efficiently decompose corn stover at low temperatures. The present study explored the key microbes of GF-20 and evaluated different culture conditions on its composition stability to promote the utilization of corn stover decomposing microbes in low temperature regions. GF-20 was subcultured to the 15th generation under different temperatures, pHs, carbon, and nitrogen sources. Then, the dynamics of fermenting pH, cellulose enzyme activities, carbohydrate concentration, and oxidation reduction potential were determined to estimate the degradation efficiency of corn stover with GF-20. Furthermore, the structural stability and functional microbes of GF-20 were identified on the basis of PCR-denaturing gradient gel electrophoresis (DGGE) profiling and principal component analysis. The results showed that the offspring of GF-20 subcultured under different temperatures (4–30°C) and pH (6.0–9.0) conditions maintained stable growth, decomposition function, and composition structure. Furthermore, consortia GF-20 had a stable composition structure, which induced GF-20 to secrete cellulose and promote substrate decomposition as corn stover and ammonium were used as sources of carbon and nitrogen, respectively. According to the PCR-DGGE profiles, the key strains of GF-20 were determined to be Bacillus licheniformis, Cellvibrio mixtus subsp. mixtus, Bacillus tequilensis, Clostridium populeti, and Clostridium xylanolyticum.